One Reasoning and Four Observations about the Europe of the Euro and about European Hospitality - Adinolfi, Massimo (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The essay proposes some reflections upon the figure of the “guest”, a figure that Davide Tarizzo’s theoretical contribution tries to define in order to open a space that could conserve political subjectivity, however weak, for Europe and its institutional structures. Tarizzo seems to be proposing the theme of European hospitality as a political invention to be activated in order to contain the repercussions of the inevitable end of the single currency. The idea is, in general, appreciated and supported in this paper, with the conviction that it follows the main course of the construction of the European Union and that it contains a reason of erosion of the political weight of the single national subjectivities. However, there is reason to doubt that the proposal of defining the juridical profile of the European guest – as separated from national citizenship – is to be linked to the post-euro scenario. In other words, the doubt is that, if this scenario should occur, the proposal could not eventually be put de facto into practice.
Keywords: Euro crisis; sovereingnty; European hospitality; national citizenship; European integration